2010
DOI: 10.1128/jvi.02081-09
|View full text |Cite
|
Sign up to set email alerts
|

Simian Rotaviruses Possess Divergent Gene Constellations That Originated from Interspecies Transmission and Reassortment

Abstract: Group A rotaviruses (RVs) are a major cause of acute dehydrating diarrhea in infants and children under the age of 5 years worldwide. These infections lead to approximately 527,000 deaths each year, the vast majority occurring in developing countries (33). RVs are also responsible for gastroenteritis in many other animal species, notably mammals and birds (16,38). RVs are members of the family Reoviridae and possess a genome consisting of 11 segments of double-stranded RNA (dsRNA). The prototypic genome of a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 48 publications
2
56
0
2
Order By: Relevance
“…Worldwide, the majority of human RVA strains possess either the Wa-like genogroup 1 constellation (I1-R1-C1-M1-A1-N1-T1-E1-H1) or the DS-1-like genogroup 2 constellation (I2-R2-C2-M2-A2-N2-T2-E2-H2) that are believed to have a common origin with the porcine and the bovine RVAs, respectively (Matthijnssens et al , 2008). A smaller group of RVA strains have the AU-1-like genogroup 3 constellation (I3-R3-C3-M3-A3-N3-T3-E3-H3) that is believed to have originated from feline RVAs (Matthijnssens et al , 2008, 2010). Currently, genotypes are assigned based on percentage nucleotide identity of at least 50 % length of the ORF.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the majority of human RVA strains possess either the Wa-like genogroup 1 constellation (I1-R1-C1-M1-A1-N1-T1-E1-H1) or the DS-1-like genogroup 2 constellation (I2-R2-C2-M2-A2-N2-T2-E2-H2) that are believed to have a common origin with the porcine and the bovine RVAs, respectively (Matthijnssens et al , 2008). A smaller group of RVA strains have the AU-1-like genogroup 3 constellation (I3-R3-C3-M3-A3-N3-T3-E3-H3) that is believed to have originated from feline RVAs (Matthijnssens et al , 2008, 2010). Currently, genotypes are assigned based on percentage nucleotide identity of at least 50 % length of the ORF.…”
Section: Introductionmentioning
confidence: 99%
“…A uniform classification system exists for each of the 11 RVA gene segments (VP7, VP4, VP6, VP1-VP3, NSP1-NSP5) defining G-, P-, I-R-, C-, M-, A-, N-, T-, E-and H-genotypes, respectively (Matthijnssens et al, 2008). Despite this seemingly close host range restriction, RVA strains are known to frequently cross the host species barrier, resulting in the detection of RVA strains unusual to that host species (Matthijnssens et al, 2010;Mino et al, 2013;Khamrin et al, 2009). Often, but not always, such inter-host species transmissions are dead-end infections.…”
mentioning
confidence: 96%
“…For example, Matthijnssens et al (2008a) demonstrated that Wa-like human rotaviruses and porcine rotaviruses have a common origin and that DS-1-like human rotaviruses and bovine rotaviruses have a common origin. More recently, determination of the complete genome sequences of simian rotaviruses indicated that simian rotaviruses are of diverse ancestry that originated largely by interspecies transmission and reassortment with non-human animal rotaviruses (Matthijnssens et al, 2010b). Furthermore, several studies have provided evidence for naturally occurring reassortants between humans and animals by analysis of whole genomes of rotavirus strains (Bányai et al, 2009;Esona et al, 2009;Ghosh et al, 2010;Matthijnssens et al, 2008cMatthijnssens et al, , 2009Matthijnssens et al, , 2010aMukherjee et al, 2009;Tsugawa & Hoshino, 2008).…”
Section: Introductionmentioning
confidence: 99%